Implementasi Program Bantuan Pangan Non Tunai di Desa Limau Manis Kecamatan Tanjung Morawa Kabupaten Deli Serdang - Murzha, Zhafira Suha; Saraan, Muhammad Imanuddin Kandias (Innovative: Journal Of Social Science Research, 2025)
This study aims to determine the implementation of the Non-Cash Food Assistance Program in Limau Manis Village, Tanjung Morawa District, Deli Serdang Regency. The analysis method used is descriptive qualitative with data collection techniques in the form of observation, interviews, and documentation. Data analysis was conducted based on four indicators from Smith's (2001) policy implementation theory, namely idealized policies, target groups, implementing organizations, and environmental factors. Translated with DeepL.com (free version)The results of this study show that the idealized policy has been implemented in accordance with the objectives of the BPNT Program. The target group of the BPNT program in Limau Manis Village has not been optimally served due to inaccurate data on participants. This causes the distribution of assistance to be often constrained, so that the program's goal of improving community welfare has not been achieved optimally. The competence of the personnel of the implementing organization, the Deli Serdang Regency Social Service already understands the BPNT Program and on environmental factors there is still a lack of socialization carried out for direct visits to KPM homes. The Deli Serdang District Social Service has conducted an evaluation in the sub-district through the Sub-district Performance Evaluation (EKK) activity to ensure that the implementation of the BPNT Program can run better in the future.